Development of semi-continuous mesocarp and nut separator in enhancing the recovery of crude palm oil - Wondi, Mohd Hafizz (2020)
Current palm oil milling process involves digestion and pressing of the whole oil palm fruitlets. However, the coexistence of mesocarp fiber and nut during pressing could lead to inevitable oil loss in fiber and nut breakage. Separation of palm mesocarp fiber from nut prior to digestion and pressing is foreseen as a potential solution to solve the problem. Therefore, a Semi-continuous Palm Mesocarp and Nut Separator machine to enhance the recovery of crude palm oil has been developed. The first part of the study was to determine the physical (mass, dimension and density) and mechanical properties (rupture force, deformation, hardness and rupture energy) of the fruitlets (whole fruit, nut and kernel). The results were used to determine the design parameters for the separator machine. The machine consists of two steps process for every cycle. The first step was to cut and remove the mesocarp fiber from its nut (seed) as well as to remove all the mesocarp produced from the process whereas the second step was to discharge the nut. A performance evaluation was conducted on the developed machine under different conditions; speed (700, 900, 1100, 1300 and 1500 rpm) and processing time (20, 30 and 40 s). The best condition, which was at 1500 rpm of speed and 40 s of separation time, was tested further under different loadings (2.50, 3.75 and 5.00 kg). Further, Response Surface Methodology (RSM) optimization was carried out to obtain the optimum process parameters to achieve maximum separation efficiency and minimum percentage of broken nut. The results showed that the ideal separation was obtained at a separation speed of 1100 rpm, 30 s of time and 2.50 g of loading mass. Under this processing condition, the machine could achieve 94.89 % of separation efficiency and 4.29 % of broken nut. Furthermore, the oil content and oil quality (FFA, DOBI, carotene content and colour) of the extracted oil from the separated mesocarp were also evaluated. The results revealed that the oil complies with the Malaysian Palm Oil Board (MPOB) standard. Increasing the digestion time from 0 to 60 minutes reduced the mesocarp oil content significantly from 100 % to 72.19 %. Overall, this study has successfully developed an effective mesocarp and nut separator machine to obtain high oil recovery with minimal nut breakage. The results from this study are valuable to the palm oil industry. If the system is successfully implemented in the industry, some processes in kernel processing plant, such as winnowing and nut polishing, can be skipped since the nut is already isolated from the mesocarp.